2016
DOI: 10.1007/s11934-016-0602-6
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Minimally Invasive Surgery and Their Management

Abstract: Minimally invasive surgery, including both traditional laparoscopic and robot-assisted laparoscopic approaches, has increasingly become the standard of care for urologic abdominal and pelvic surgery. This is a comprehensive review of the contemporary literature regarding complications of laparoscopic and robotic urologic surgery. The review highlights pertinent studies with the goal of providing the minimally invasive urologic surgeon with an up-to-date overview of general and procedure-specific complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Trocar puncture accidents are rare but associated to high morbidity due to viscera lesion or even mortality in cases of vascular injury. 1214 The technique is also of some importance for safe trocar insertion, in addition to the characteristics of the trocar itself. Some systematic review compared different laparoscopic entry techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Trocar puncture accidents are rare but associated to high morbidity due to viscera lesion or even mortality in cases of vascular injury. 1214 The technique is also of some importance for safe trocar insertion, in addition to the characteristics of the trocar itself. Some systematic review compared different laparoscopic entry techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This type of injury would occur outside of the view shown on the surgical monitor, which could delay its diagnosis. Some investigators have studied organ injuries that occur during laparoscopic surgery and found that measurable injuries that are diagnosed after surgery can lead to serious morbidities 5‐7 . In general, numerous instrument insertions are performed during laparoscopic and robotic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes the condition becomes worse leading to increased readmission rates after patient discharge from the hospital as a result of the previously mentioned issue. POI reflectively represents a major source of economic burden with high cost on patient and financial burden on health care facilities [4,5].…”
Section: Introductionmentioning
confidence: 99%